2007
DOI: 10.1029/2007gl030635
|View full text |Cite
|
Sign up to set email alerts
|

Meteor smoke particle properties derived from Arecibo incoherent scatter radar observations

Abstract: [1] We present a new algorithm to infer information on the properties of charged meteoric smoke particles (MSPs) from the shape of incoherent scatter radar spectra. We show that in the presence of charged MSPs the spectrum can be approximated as the sum of two Lorentzians. These two distinct spectral lines correspond to two diffusion modes in the D-region plasma, i.e., one due the presence of positive ions and one because of heavy charged MSPs. The widths and amplitudes of these two spectral lines yield inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 20 publications
2
69
0
Order By: Relevance
“…Among these are the nucleation of mesospheric ice particles (e.g., Rapp and Thomas, 2006), the mesospheric metal chemistry , the D-region charge balance (e.g., Rapp and Lübken, 2001), the heterogeneous formation of water vapour in the mesosphere (Summers et al, 2001), and even the nucleation of polar stratospheric cloud particles which play a major role in the formation of the ozone hole (e.g., Voigt et al, 2005). While some progress regarding the experimental investigation of these atmospheric trace species has been made over the past years with sounding rockets (e.g., Schulte and Arnold, 1992;Gelinas et al, 1998;Horányi et al, 2000;Rapp et al, 2005;Lynch et al, 2005;Barjatya and Swenson, 2006;Amyx et al, 2008;Strelnikova et al, 2009;Rapp et al, 2010), incoherent scatter radars Strelnikova et al, 2007;Fentzke et al, 2009), satellites (Hervig et al, 2009(Hervig et al, , 2012, and laboratory studies (Saunders and Plane, 2006), much of our knowledge about these particles still relies on model results (e.g., Hunten et al, 1980;Gabrielli et al, 2004;Megner et al, 2006Megner et al, , 2008Bardeen et al, 2008). Among other things, very little is still known about the physical and chemical properties of MSPs such as their composition and their electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among these are the nucleation of mesospheric ice particles (e.g., Rapp and Thomas, 2006), the mesospheric metal chemistry , the D-region charge balance (e.g., Rapp and Lübken, 2001), the heterogeneous formation of water vapour in the mesosphere (Summers et al, 2001), and even the nucleation of polar stratospheric cloud particles which play a major role in the formation of the ozone hole (e.g., Voigt et al, 2005). While some progress regarding the experimental investigation of these atmospheric trace species has been made over the past years with sounding rockets (e.g., Schulte and Arnold, 1992;Gelinas et al, 1998;Horányi et al, 2000;Rapp et al, 2005;Lynch et al, 2005;Barjatya and Swenson, 2006;Amyx et al, 2008;Strelnikova et al, 2009;Rapp et al, 2010), incoherent scatter radars Strelnikova et al, 2007;Fentzke et al, 2009), satellites (Hervig et al, 2009(Hervig et al, , 2012, and laboratory studies (Saunders and Plane, 2006), much of our knowledge about these particles still relies on model results (e.g., Hunten et al, 1980;Gabrielli et al, 2004;Megner et al, 2006Megner et al, , 2008Bardeen et al, 2008). Among other things, very little is still known about the physical and chemical properties of MSPs such as their composition and their electrical and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Typical values for Sc found in PMSEs are several hundred on average and can often be several thousands (Lübken et al, 1994;Li et al, 2010;Rapp et al, 2011;Strelnikov and Rapp, 2011). The same mechanism but involving MSPs was proposed to explain the PMWEs in the case when neutral turbulence is not sufficiently large (e.g., Kavanagh et al, 2006;Lübken et al, 2007;Kero et al, 2008;La Hoz and Havnes, 2008;Havnes and Kassa, 2009;Havnes et al, 2011;Strelnikova and Rapp, 2013;Stebel et al, 2004;Belova et al, 2008). The latter has not yet been confirmed by direct measurement.…”
Section: Discussionmentioning
confidence: 96%
“…It has been shown that MSPs are important for the D-region charge balance (Friedrich et al, 2011Baumann et al, 2013Baumann et al, , 2015Robertson et al, 2014;Asmus et al, 2015). Moving with the background flow and bound to neutral air turbulence, charged MSPs are also suggested to be potentially involved in the formation of so-called polar mesospheric winter echoes (PMWEs) (e.g., Kavanagh et al, 2006;Lübken et al, 2007;Kero et al, 2008;La Hoz and Havnes, 2008;Havnes and Kassa, 2009;Havnes et al, 2011;Strelnikova and Rapp, 2013;Stebel et al, 2004;Belova et al, 2008). There are also theories explaining the formation of PMWEs by neutral turbulence and an increased electron density (e.g., Lübken et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These MSPs are particles, which originate from extraterrestrial matter that is injected into the atmosphere by evaporating meteors (Rosinski and Snow, 1961;Megner et al, 2006). The existence of these MSPs was proven by in situ measurements on sounding rockets (e.g., Havnes et al, 1996;Rapp et al, 2012), by spectrometers on board satellites (Hervig et al, 2009) and by means of incoherent-scatter radars (Strelnikova et al, 2007). MSPs have effects on the nucleation of ice particles in the mesosphere (e.g., Wilms et al, 2016, and references therein) and influences on the ionospheric charge balance Baumann et al, 2013;Plane et al, 2014;Asmus et al, 2015) and ion chemistry (Baumann et al, 2015) of the D region.…”
Section: Introductionmentioning
confidence: 99%